1997
DOI: 10.1007/bfb0029236
|View full text |Cite
|
Sign up to set email alerts
|

Rigid registration of CT, MR and cryosection images using a GLCM framework

Abstract: Abstract. The majority of the available rigid registration measures are based on a 2-dimensional histogram of corresponding grey-values in the registered images. This paper shows that these features are similar to a family of texture measures based on Grey Level Cooccurrence Matrices (GLCM). Features from the GLCM literature are compared to the current range of measures using images from the visible human data set. The voxel-based rigid registration of Cryosection and CT images have not been reported before. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The heuristic criterion devised by Woods et al [21] was originally intended for PET-MR registration, but it has also been used with other modalities [2]. This turns out to be very similar to the correlation ratio.…”
Section: Woods Criterionmentioning
confidence: 84%
See 3 more Smart Citations
“…The heuristic criterion devised by Woods et al [21] was originally intended for PET-MR registration, but it has also been used with other modalities [2]. This turns out to be very similar to the correlation ratio.…”
Section: Woods Criterionmentioning
confidence: 84%
“…Even so, 2 we can identify two differences. First, the correlation ratio sums variances, a~ whereas the Woods criterion sums normalized standard deviations, aJmi.…”
Section: Woods Criterionmentioning
confidence: 99%
See 2 more Smart Citations
“…This category is not fundamentally different from the previous one, as the ideal case is still perfect functional dependence; mutual information is however theoretically more robust to variations with respect to this ideal situation. A number of comparison studies have shown that similarity measures yield different performances depending on the considered modality combinations [22,2,13,10,15]. There is probably no universal measure and, for a specific problem, the point is rather to choose the one that is best adapted to the nature of the images.…”
Section: ρ(I J) = Cov(i J) Var(i) Var(j)mentioning
confidence: 99%